Exploration of CircuitVerse from VLSI Cutting-edge Perspective - Sutapa Sarkar
Efficient digital simulators set the very large-scale integration (VLSI) design process one step easier by augmenting scalability, circuit reusability, testability, code portability, and so on. Cloud-based open source CircuitVerse simulator is supplemented with a versatile hardware component library. This instructional simulator can introduce a lot for the improvement of performance scaling metrics of digital designs. The novelty of this work is to uniquely correlate the flow integrity in CircuitVerse with digital VLSI-fronted design. A way to the optimization of design complexity and hardware requirements is achieved alongside.